Severe asthmatic airways have distinct circadian clock gene expression pattern associated with WNT signaling - Tran, Nguyen Quoc Vuong; Le, Minh Khang; Nakamura, Yuki; Nakao, Atsuhito (Clinical and translational allergy, 2024)
[...]the lack of information on specific sampling times restricted our analysis although bronchial epithelial brushing samples are likely collected during regular operation hours and we have considered diurnal variations in our analysis (Figure 1C). [...]we cannot exclude potential influence of asthma treatment including corticosteroid, 10 since most patients in the datasets, except for GSE67472, were on asthma medication. In summary, we show that severe asthmatic airways have distinct circadian clock gene expression patterns associated with WNT signaling, a crucial pathway for airway remodeling in asthma. [...]disturbance of airway circadian clock activity may be one of the determining features of severe asthma.